Adaptive behavior of farmers' livelihoods in the context of human-environment system changes. (June 2020) - Yin, Sha; Yang, Xinjun; Chen, Jia
Abstract: Understanding the adaptive behavior of farmers' livelihoods is vital to the explanation of how farmers adapt to changes caused by the human-environment system. This study constructed a new conceptual framework to analyze farmers' livelihood adaptation and selected Minqin in the arid region of northwest China, as a case to explore farmers' adaptive behaviors and their influencing factors. Social surveys in thirteen townships of the county were conducted and 582 valid questionnaires and 32 valid interviews were collected. The findings show that government policies promoted changes in the rural human-environment system. Subsequently, farmers' use of natural resources decreased, planting structures were adjusted, and the government provided more resources to support farmers' livelihoods. Farmers' choice of adaptive behaviors was based on the socio-economic characteristics of their households. Traditional agriculture adjustment was the preferred adaptive behavior. External factors, including afforestation areas; effective irrigation rates; labor training and agricultural technicians; and farmers' livelihood capital, such as education and awareness, natural capital, income and expenditure, and social networks, were significant drivers of the adoption of diverse adaptive behaviors. The results indicate that the government's adaptive measures and farmers' adaptive behaviors both need to be incorporated into the policymaking process for ecological restoration and rural development. Highlights: A new conceptual framework was constructed for farmers' livelihood adaptive behavior. Both external and internal factors affected farmers' choice of adaptive behavior. Traditional agriculture adjustment was the preferred adaptive behavior. Agricultural technicians and afforestation areas had vital influence on farmers' adaptive behavior. Education and awareness were the most internal significant drivers of the adoption of diverse adaptive behaviors.